2019
DOI: 10.1111/ijd.14462
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans with fibrosarcomatous transformation: our experience, molecular evaluation of selected cases, and short literature review

Abstract: Dermatofibrosarcoma protuberans with fibrosarcomatous transformation (DFSP-FS) is a higher grade tumor arising from dermatofibrosarcoma protuberans (DFSP). Recent literature highlights its impact on recurrence rates, metastatic rates, and survival. In this article, we aim to describe our experience with 13 cases of DFSP-FS in terms of pathologic findings, molecular alterations, clinical outcomes, management, and also perform a short recent literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The histopathological differential diagnosis of DFSP includes various spindle cells neoplasms such as dermatofibroma, solitary fibrous tumor, spindle cell lipoma, schwannoma, synovial sarcoma, spindle cell melanoma or sarcomatoid carcinoma. Extensive immunohistochemistry analysis usually suffices for establishing the correct diagnosis, but in rare cases, molecular analysis can be required [1,6,17]. Molecular studies have demonstrated that DFSP displays a characteristic t(17;22)(q22;q13) leading to the formation and overexpression of the fusion gene COL1A1-PDGFB, and subsequently to activation of PDGF receptor [1,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The histopathological differential diagnosis of DFSP includes various spindle cells neoplasms such as dermatofibroma, solitary fibrous tumor, spindle cell lipoma, schwannoma, synovial sarcoma, spindle cell melanoma or sarcomatoid carcinoma. Extensive immunohistochemistry analysis usually suffices for establishing the correct diagnosis, but in rare cases, molecular analysis can be required [1,6,17]. Molecular studies have demonstrated that DFSP displays a characteristic t(17;22)(q22;q13) leading to the formation and overexpression of the fusion gene COL1A1-PDGFB, and subsequently to activation of PDGF receptor [1,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive immunohistochemistry analysis usually suffices for establishing the correct diagnosis, but in rare cases, molecular analysis can be required [1,6,17]. Molecular studies have demonstrated that DFSP displays a characteristic t(17;22)(q22;q13) leading to the formation and overexpression of the fusion gene COL1A1-PDGFB, and subsequently to activation of PDGF receptor [1,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The present pediatric case (defined as FS-DFSP in a patient under the age of 21) is the twelfth to have been reported in the literature (Table 1). [8][9][10][11][12][13][14][15][16][17] Examining the reported pediatric patients, the median age was 12.5 years [range: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and a slight male predominance (male: female ratio 1. MIB-1 proliferation index, and low CD34 expression ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Disease recurrence has a higher degree of local infiltration, tissue destruction, and fibrosarcomatous transformation 4. Fibrosarcomatous DFSP is a rare pathologic variant with a more aggressive infiltrative growth and higher rate of metastasis 5. Morphologically, the transformed variant shows fascicular to herringbone growth with higher degree of pleomorphism and mitotic activity.…”
Section: Introductionmentioning
confidence: 99%